Berita Online Sebagai Instrumen Dakwah: Antara Profetik dan Provokatif - Efa Rubawati (LPPM IAIN Sorong, 2018)
The presenting of internet as the new media with high interactivity and connectivity, the fact has made almost the humans life undergoes the changing. It is not except for dimension of religion. The one of religion activity is preaching undergoing transformation from the conventional media to new media. Presently, a lot of online news in one side gives positive effect in deployment the fast and broad information, but in other side it becomes the place of developing the news false (hoax). Although, the news online is many still entering the preaching’s messages in its news. One of them is serambinews.com dan panjimas.com. The study in this paper uses a study through descriptive method with framing media analysis. Sources of data were obtained from various sources and references related to the topic of discussion, both are from online internet and book literature. This study finds important things such as preaching of bil qalam can be done through news, although in the delivery of messages of preaching, these two online media have different framing. Understandably, serambinews.com conveys prophetic messages to the reader through the news, while panjimas.com chooses to present it provocatively. Both have their own advantages and disadvantages, which can be adapted to theconditions and assumptions of the community as mad'u